The Dynamics Of Space Struggles Over The Lae-Lae Island Reclamation Project In Makassar City - Sopian Tamrin; Riri Amandaria; Idham Irwansyah; Najamuddin Najamuddin (Jurnal Mamangan, 2024)
The planned reclamation of Lae-Lae Island undoubtedly poses a threat to the marine ecosystem and the livelihoods of the surrounding fishing communities. This research aims to depict the dynamics of spatial contestation arising from this situation. To elucidate these dynamics, the researcher employs Henri Lefebvre's sociology of space and Edward Soja's geographical imagination. Utilizing a qualitative descriptive approach, data were gathered through observation, interviews, and documentation involving twenty-three informants. Findings reveal the dynamics of spatial contestation on Lae-Lae Island, including the emergence of spatial awareness as a socio-economic arena and the mobilization of resources from both the island community and external parties. Internal mobilization, led by community leaders, actively fosters solidarity among residents in rejecting the reclamation, while external resource mobilization involves actors from environmental organizations, media, and academia. The research concludes that community resistance stems from the direct implications of reclamation on residents' living space and livelihoods, particularly those of fishermen. The integration of Henri Lefebvre's sociological analysis and Edward Soja's geographical imagination provides a fresh perspective on social movement phenomena and spatial contestation.